Case Study On KAF-Seagroatt And Campbell Berhad - Wong, Yew Huat (2005)
The stock brokering industry in Malaysia has been protected from foreign competition. It is worthwhile to run a thorough diagnosis on the company and subsequently highlight the future strategies needed to continue operates in a more open and competitive environment.